Mental Health, Bullying, and Victimization among Chinese Adolescents - Yang Wen; Xihe Zhu; Justin A. Haegele; Fangliang Yu (Children, 2022)
The purpose of this study was to examine if adolescents who experience anxiety or depression have higher levels of reported bullying victimization or perpetration than those who do not. Based on the existing research, we hypothesized that those who experienced moderate or severe depression and anxiety would have higher rates of bullying victimization and perpetration when compared to those who experienced mild or no depression. This study used an observational design, and data were collected from a convenience sample of adolescents in a large regional high school in an Eastern province of China. The final sample included 1481 adolescents aged 14–19 years who provided complete data for each of the study variables. Demographic data were collected through a four-item demographic survey, bullying perpetration and victimization data were collected using subscales from the Illinois Bully Scale, and anxiety and depression were measured using the Chinese version of the General Anxiety Disorder-7 scale and the Patient Health Questionnaire, respectively. Descriptive analyses, correlational analyses, and multivariate analysis of covariance were used to analyze the data. About 7.1% and 15.2% of participants reported moderate-to-severe depression or moderate-to-severe anxiety, respectively. Pairwise comparisons indicated that adolescents with no or mild depression had significantly lower bullying perpetration than those with moderate-to-severe depression, but those with no or mild anxiety had significantly higher perpetration than those with moderate-to-severe anxiety. There was no statistically significant difference in victimization among different anxiety or depression levels alone (all p-values ≥ 0.05). This is among the first studies to examine reported levels of bullying perpetration and victimization among adolescents experiencing anxiety and depression. The findings help to identify adolescents who experience moderate-to-severe levels of depression as an at-risk group for bullying perpetration, who should therefore be a focus of bullying intervention work.